Female versus male biological identities of nanoparticles determine the interaction with immune cells in fish. Issue 4 (3rd March 2017) - Hayashi, Yuya; Miclaus, Teodora; Murugadoss, Sivakumar; Takamiya, Masanari; Scavenius, Carsten; Kjaer-Sorensen, Kasper; Enghild, Jan J.; Strähle, Uwe; Oxvig, Claus; Weiss, Carsten; Sutherland, Duncan S.
Abstract : Sex- and species-specific biological identities of nanoparticles determine cellular recognition and uptake by leukocytes in fish in vitro . Abstract : Biomolecule decoration of nanoparticles provides a corona that modulates how the nanoparticles interact with biological milieus. The corona composition has proved to reflect the differences in the repertoire of proteins to which the nanoparticles are exposed, and as a result the same nanoparticles can acquire a differential biological identity. Here we examined whether a unique biological identity acquired from sex-specific protein repertoires could alter the degree of nanoparticle uptake by cognate immune cells. We chose zebrafish as a model species of which blood plasma is sexually contrasted by the unique presence/absence of the egg yolk precursor protein vitellogenin. Sex-specific protein coronas were thus formed around 70 nm SiO2 nanoparticles using female/male blood plasma from zebrafish or fetal bovine serum as a non-native reference. In contrast to protein coronas formed of male blood plasma, a "female" biological identity of the nanoparticles was represented by prevailing contribution of vitellogenins to the corona proteome. We then exposed zebrafish blood cells to the three types of pre-formed nanoparticle–protein complexes and compared nanoparticle uptake using flow cytometry. Lymphoid and myeloid populations of the blood cells preferentially accumulated the nanoparticles with a female biological identity, irrespective of the sex of the fish from which the cells were obtained. The concept of repertoire differences in the corona proteome therefore deserves further attention, as various factors such as sex-specific biological conditions exemplified in this study could alter the nanoparticle–cell interactions.